Theoretical Principles of Forecasting Accident Rate in the Conflict Sections of the Cities by the Method of Potential Danger - Dzianis Kapski; Ivan Leonovich; Kornelija Ratkevičiūtė (The Baltic Journal of Road and Bridge Engineering)
The article describes an attempt to apply a catastrophe theory for the process of road transport situation development into a conflict situation, which, in the result turns to the accident, through the interpretation of a potential danger of the conflict. For this purpose the simplest methods (elementary catastrophes) were used, allowing to estimate the values of the basic parameters of road traffic. The suggested method made it possible to take into consideration the interaction of conflict points in joint location, what has considerably increased the adequacy of forecasting.